TOPONYMIC LANDSCAPE AND PROBLEMS RELATED TO CHANGING IT - Starostenkov (Revista Inclusiones, 2020)
In the paper the problems that arise when changing geographical names have been considered, the conclusion about the regularity and continuity of this process has been substantiated, the course and consequences of changing geographical names as an important element of the symbolic revolution have been studied by using a lot of factual materials, and some recommendations to mitigate the risks of color revolutions have been given.